2021
DOI: 10.3390/diagnostics11050843
|View full text |Cite
|
Sign up to set email alerts
|

Force-Invariant Improved Feature Extraction Method for Upper-Limb Prostheses of Transradial Amputees

Abstract: A force-invariant feature extraction method derives identical information for all force levels. However, the physiology of muscles makes it hard to extract this unique information. In this context, we propose an improved force-invariant feature extraction method based on nonlinear transformation of the power spectral moments, changes in amplitude, and the signal amplitude along with spatial correlation coefficients between channels. Nonlinear transformation balances the forces and increases the margin among th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…Health professionals are more enthusiastic about using their advantages of flexibility and self-learning capacity as an aiding system for reliable performance. Intelligent systems based on ML algorithms have been intensively investigated for various biomedical systems, focusing on disease detection and risk reduction [ 16 , 17 , 18 , 49 , 50 ]. Like other severe diseases, CKD has piqued the interest of researchers in creating ML-based diagnosis systems for CKD [ 3 , 13 , 18 , 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Health professionals are more enthusiastic about using their advantages of flexibility and self-learning capacity as an aiding system for reliable performance. Intelligent systems based on ML algorithms have been intensively investigated for various biomedical systems, focusing on disease detection and risk reduction [ 16 , 17 , 18 , 49 , 50 ]. Like other severe diseases, CKD has piqued the interest of researchers in creating ML-based diagnosis systems for CKD [ 3 , 13 , 18 , 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intelligent systems based on ML algorithms have been intensively investigated for various biomedical systems, focusing on disease detection and risk reduction [ 16 , 17 , 18 , 49 , 50 ]. Like other severe diseases, CKD has piqued the interest of researchers in creating ML-based diagnosis systems for CKD [ 3 , 13 , 18 , 20 , 21 , 22 ]. However, their application in developing prediction models for CKD in type 1 diabetic mellitus patients is rare.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…to addressing multiple challenging factors, several pieces of research are found on muscle force variation. Recently, Islam et al [15] proposed a non-linear scaling-based feature extraction method to resolve the muscle force variation of transradial amputees employing 84-dimensional feature space. Again, Islam et al [14] extended their previous work and introduced a novel signal normalization scheme to overlap the extracted features of different muscle force levels.…”
Section: Table 1 (Continued)mentioning
confidence: 99%
“…Moreover, short-time Fourier transforms or wavelet transforms extract features both in time and frequency domains. However, in the literature, time-domain features are used more frequently than frequency-or time-frequency-domain features since these features do not require any transformations and hence large computing resources, such as processing power and memory [25,36]. Consequently, this research is carried out to determine a further contribution to the time-domain feature set.…”
Section: Introductionmentioning
confidence: 99%